EFFECTS OF HIGH INTENSITY LASER THERAPY AND SHOCKWAVE ON PAIN, ROM AND FUNCTIONAL DISABILITY IN PATIENTS WITH POST ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION SURGERY (Review Journal of Neurological & Medical Sciences Review, 2026)
Background: Anterior cruciate ligament (ACL) reconstruction is commonly performed to restore knee stability; however, postoperative pain, reduced range of motion (ROM), and functional disability remain significant challenges during rehabilitation. Objective: To compare the effects of high-intensity laser therapy and extracorporeal shockwave therapy on pain, ROM, and functional disability in patients following ACL reconstruction.Methods: This randomized controlled trial was conducted and 38 patients aged 18–40 years who had undergone ACL reconstruction enrolled. Participants were randomly allocated into two groups: Group A (HILT, n=19) and Group B (ESWT, n=19). Both groups received standardized rehabilitation in addition to their respective interventions for 6 weeks. Outcomes were assessed using the Numeric Pain Rating Scale (NPRS), goniometric measurement of knee ROM, and the Knee Injury and Osteoarthritis Outcome Score (KOOS). Results: Both groups showed significant improvements in all outcome measures (p